1994
DOI: 10.1111/j.1528-1157.1994.tb02448.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Valproate and Phenytoin on Cognitive Function in Elderly Patients: Results of a Single‐Blind Randomized Comparative Study

Abstract: Thirty-eight patients (median age 77 years; range 62-88 years) with elderly-onset seizures were entered into a single-blind, randomized study designed to compare the impact of phenytoin (PHT) and valproate (VPA) on cognitive function. A stratified minimization program matched the two groups for age, sex, and seizure type. Attention, concentration, psychomotor speed, and memory were assessed twice before treatment (to minimize practice effects), at 6 weeks and (for patients remaining in the study) at 3 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
8

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 22 publications
3
53
0
8
Order By: Relevance
“…These results were agreed with Mattson et al, 1985 [22], who reported that there was more difficulties in cognitive functions with phenytoin as compared with carbamazepine in partial and secondary generalized seizures. Regarding the psychotic behavior problems there was no significant differences between the three groups, in agreement with studies done by Sabers et al 1995 [23] and Craig and Tallis 1994 [24] who found no differences between antiepileptic drugs as regards their effect on cognitive functions in epileptic adolescents.…”
Section: Discussionsupporting
confidence: 81%
“…These results were agreed with Mattson et al, 1985 [22], who reported that there was more difficulties in cognitive functions with phenytoin as compared with carbamazepine in partial and secondary generalized seizures. Regarding the psychotic behavior problems there was no significant differences between the three groups, in agreement with studies done by Sabers et al 1995 [23] and Craig and Tallis 1994 [24] who found no differences between antiepileptic drugs as regards their effect on cognitive functions in epileptic adolescents.…”
Section: Discussionsupporting
confidence: 81%
“…More favourable findings include minimal cognitive effects in children [Forsythe et al 1991] and elderly patients [Craig and Tallis, 1994], improvements in Stroop performance in partial epilepsy [Bittencourt et al 1993], no differences on tasks assessing verbal and performance intelligence, memory and visuomotor function, before and after treatment in drug-naïve adult patients [Sudhir et al 1995] and a similar cognitive profile to oxcarbazepine [Aikiä et al 1992].…”
Section: Phenytoinmentioning
confidence: 99%
“…Тем не менее, в отдельных исследованиях было показано отрица-тельное влияние вальпроата (по выраженности -от легкого до умеренного) на скорость психомоторных реакций и скорость мыслительных процессов [28,29,38,66,81].…”
Section: старые антиэпилептические препаратыunclassified